Public Service Procedures (Case Study of Handling Services for Making Cover Letters for Birth Certificates in Bareng Village, Klojen District, Malang City) - Didik Supriyanto (Westscience Press, 2023)
This research was conducted at the Bareng Village office. The purpose of this study was to determine public service procedures at the Bareng Village Office, Klojen District, Malang City. The results of this study indicate that 1) Procedures for handling birth certificate delivery services at the Bareng Village office, Klojen District, Malang City include: a) submitting a birth certificate application and providing the application form by the service officer. Submission of requests by the community is not difficult and not complicated. b) Examination of files by service officers. There were no problems with examining the files, the officers carried out according to the existing procedures, namely checking one by one the completeness of the requirements starting from birth certificates, family cards, ID cards, and diplomas. c) Filling out the register book and expedition book. During the process of filling out the registration book and expedition book, the officers did not experience any problems. d) Preparation of an application letter signed by the village head. There is no problem in preparing a cover letter for making a birth certificate introduction. 2) the inhibiting factor that many officers face is the community, which lacks participation in the awareness to complete the requirements in making an introduction to a birth certificate. Supporting factors in the service procedure for making birth certificate introductions are the existence of clear laws, the officers who handle them are by the SOPs that have been set in the Village